Askin's Tumor: A Dual Case Study - Bikash Shrestha; Bhupendra Nath Kapur; Kavita Karmacharya; Sunita Kakkar; Ranjit Ghuliani (International Journal of Pediatrics)
Askin's tumor is a rare tumor arising from the chest wall. It is a subset of Ewing sarcoma characterized histologically by the presence of small round blue cells. It is a highly malignant tumor with guarded prognosis, which is dependent upon the extension of tumor at the time of diagnosis. A dual paper of Askin's tumors in young boys is being presented here.